A critical analysis on Housing And Development (Control And Licensing) (Amendment) Act 2012: criminalised abandonment of housing projects. / Mohamad Shahrizzat Amadan, Wan Ahmad Hijrah Wan Abdullah and Najwa Abd Malek - Amadan, Mohamad Shahrizzat; Wan Abdullah, Wan Ahmad Hijrah; Abd Malek, Najwa (2013)
This research project is about our analysis on Housing Development (Control and Licensing) (Amendment) Act 2012, concerning criminalized abandonment of housing projects particularly. This research project was set to point out the weaknesses existing in our current law and its enforcement in punishing the licensed housing developers in errant who are responsible for housing projects abandonment in Malaysia substantively and procedurally. Since the new amendment of the Act provides a provision that allows house buyers to initiate criminal action against the developers who fails to finish a housing project within the time stipulated in the contract, the issue is that who will take responsibility and liability of the developer company, is it going to be the shareholders, the directors or even the secretary may be held liable when there is a criminal action against the developer company by the affected house buyers. Those issues concern with Company and Criminal law. This shows that our current and newly amended law is still weak and has flaws. Since we have pointed out the flaws in the provision, we tried to suggest few good laws that had been practised in advanced country as an example for Malaysia to adopt by making a comparison the Republic of Singapore in terms of the law and enforcement. Our research project aims to provide a little bit more of protection to the house purchasers in Malaysia so that there will be less cases of abandoned housing projects in Malaysia in the future.